A BRIEF REVIEW OF SIYASAH SYAR'IYYAH’S PRINCIPLES ON REASONS FOR THE AMENDMENT OF SINJAI REGENT REGULATION NUMBER 60 OF 2023 CONCERNING THE PARTICIPATION OF VILLAGE HEADS AND VILLAGE OFFICIALS IN THE BPJS HEALTH INSURANCE PROGRAM - Nurazizah Nurazizah; Andi Muh. Taqiyuddin BN; Hisbullah Hisbullah; Mustaufiq Mustaufiq; Bariek Ramdhani Pababbari (JOSH: Journal of Sharia, 2026)
This study aims to discuss a brief review based on the principles of syar'iyyah politics regarding the reasons for the amendment to Sinjai Regent Regulation Number 60 of 2023 concerning BPJS Health membership for village heads and village officials. This study is a qualitative study. The research design is field research. The supporting informants in this study consisted of the Head, Secretary, and Staff of Bonto Village, Sinjai Tengah District, Sinjai Regency, the Head of the Village Administration Division of the Sinjai Regency Community and Village Empowerment Office, and the Head of the Legal and Human Rights Division of the Sinjai Regency Secretariat. The results of this study show that the legal, philosophical, and sociological reasons for the amendment of Sinjai Regent Regulation No. 19 of 2021 to No. 60 of 2023 are in line with the principles of siyasah syar'iyyah. Among the reasons considered to be in line with these principles is the simplification of administration, which previously caused difficulties for village officials and even resulted in delays in the payment of BPJS Health contributions for village officials, ultimately leading to some village officials not receiving health services from BPJS.  However, the implications of this regulation still show inconsistencies with the principles of Siyasah Syar'iyyah. For example, there is a discrepancy with the principle of public interest, because if one village is late in uploading data, other villages are also affected, namely the system immediately experiences congestion. Health services for all village officials are also hampered. This also shows a discrepancy with the principle of justice, because there is unfair treatment of village officials who upload data on time.